KARAKTERISASI WARNA BULU DAN UKURAN TUBUH SAPI BALI JANTAN PADA PETERNAKAN RAKYAT - Rajab Rajab (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The aims of this reseach were both to identification of coat color and to characterization several body measurements of Bali cattle male categorized in three types of age which reared in traditional farming system. The study conducted by using survey observatory method with total of 154 tails of beef cattle using for coat color identification and 29 tails of male Bali cattle were measured. Observed variables were coat color, chest circumference, shoulder height and body lenght. The data obtained were analyzed descriptively. The results showed that the distribution of Bali cattle with normal coat color was 100 %, but if diveded into native and unnative color then the frequencies were 64 % and 36 % respectively. The average rate of chest circumference, shoulder height and body lenght of male Bali cattle respectively were follows 108.47, 86.92, and 84.07 cm for Io ; 120.62, 96.98, dan 96.61 cm for I1 ; and 144.75, 116.93, and 112.22 for I2 cm. The body size of male Bali cattle is still relatively low and does not meet the quality standards of good beef cattle.